Normal fetal growth profile at 10-41 weeks of gestation: an update based on 10225 normal singleton pregnancies and measurement of the fetal parameters using 3D ultrasound = Das normale fetale Wachstumsprofil zwischen 11 und 41 Schwangerschaftswochen : ein Update anhand von 10225 normalen Einzelschwangerschaften und Messung der fetalen Parameter mittels 3D-Ultraschall - Merz, Eberhard; Pashaj, Sonila; Wellek, Stefan (Ultraschall in der Medizin, 2023)
Objective: To construct new growth charts and tables for the following fetal growth parameters: biparietal diameter (BPD), occipitofrontal diameter (OFD), head circumference (HC), abdominal transverse diameter (ATD), abdominal sagittal diameter (ASD), abdominal circumference (AC), femur length (Fe), tibia length (Ti), fibula length (Fi), humerus length (Hu), radius length (Ra), and ulna length (Ul). Patients and Methods: This prospective study was conducted at a level III ultrasound center as a population-based cross-sectional study on 10 225 normal singleton pregnancies with a gestational age between 10 and 41 completed weeks. Gestational age was confirmed in all cases by an ultrasound examination with crown-rump measurement before 10 weeks of gestation. All examinations were performed with 3 D probes. BPD, OFD, ATD, and ASD were measured as outer-to-outer measurements (skin-to-skin) after identifying the exact biometric planes by 3 D multiplanar display. HC was computed using the formula HC = 2.34 × (BPD2 +OFD2) . For AC the approximate elliptical formula AC = (ATD+ASD)/2 × 3.142 was used. Measurements of the limb bones included the entire ossified shaft. Results: Based on a nonlinear regression model for the age-specific mean values, distribution-free reference ranges were calculated for the parameters BPD, OFD, HC, ATD, ASD, AC, Fe, Ti, Fi, Hu, Ra and Ul. The new reference ranges were compared with our reference ranges published in 1996 as well as with different reference charts published by other authors. Conclusion: 3 D ultrasound allows a controlled demonstration of all fetal planes required for exact biometric measurements. The fetal growth profile including the 12 biometric parameters gives a precise overview of normal or abnormal fetal growth.
Published online 01.01.2023
Gesehen am 22.05.2023